Conceptualising bereavement in profound and multiple learning disabilities. Issue 4 (3rd October 2016) - Young, Hannah
Abstract : Purpose: Bereavement and loss are key factors in poor emotional wellbeing among people with profound and multiple learning disabilities (PMLD). However, little attention has been drawn to this group in the grief and disability literature. The purpose of this paper is to make sense of bereavement and loss in people with PMLD, with reference to theoretical contributions to the field and studies of grief reactions. Design/methodology/approach: A systematic review revealed 34 relevant published works. These were analysed for relevant contributions. Findings: Three main types of theoretical contributions have been made; traditional grief theories, cognitive approaches and attachment-based perspectives. Although a limited number of case studies exist, a range of grief reactions have been reported in people with PMLD. Traditional grief theories and cognitive approaches are somewhat limited in making sense of grief responses in this group, while attachment-based perspectives may prove useful in providing theoretical and therapeutic direction. Research limitations/implications: Further research is required to more accurately describe the nature of relationships in people with PMLD. Practical implications: Major contributions to the field point to the value of facilitating engagement with the grieving process, through communication around the loss and training for staff. In addition, attachment-based perspectives are offering routes for establishing therapeutic relationships that may help to resolve behavioural difficulties. Originality/value: This paper provides an overview of the perspectives within bereavement and disability, drawing together clear theoretical frameworks for future research and practice.